Basic Profile of Child Marriage in Ghana - Malé, Chata (World Bank, Washington, DC, 2016)
This brief has provided a basic profile of child marriage in Ghana. Measures of child marriage are very high. The share of women aged 18-22 who married as children is 17.2 percent and it has declined substantially over time. The share of girls marrying very early, before the age of 15, has also declined. Other measures of child marriage have declined as well over the last 25 years. Child marriage is associated with lower wealth, lower education levels, and higher labor force participation. These are however only correlations, not necessarily causal effects. Other briefs in this series look at potential causal effects.